Oil shale development in the United States : prospects and policy issues - Bartis, James T., 1945- (RAND, 2005)
In the late 1970s and early 1980s, when crude oil prices were high, government and private-sector energy experts took a hard look at the costs and benefits of extracting oil from the vast deposits of oil shale that lie beneath the western United States (much of it under government land). Oil prices soon subsided, and interest in the topic waned. With oil prices again spiking and global demand showing no signs of abating, it makes sense to reexamine the costs and benefits of oil shale development. In this report, the authors describe the oil shale resources (estimated at more than triple the proven oil reserves of Saudi Arabia); the suitability, cost, and performance of technologies for developing these resources; and the key energy, environmental, land-use, and socioeconomic policy issues that need to be addressed by government decisionmakers. The authors conclude by outlining both the challenges and opportunities for early action with regard to those policy issues.